WORK-LIFE BALANCE AND JOB STRESS AS PREDICTORS OF JOB SATISFACTION AMONG EMPLOYEES OF THE NATIONAL SEARCH AND RESCUE AGENCY IN JAKARTA - Jabbarani Nur Majiidu; Puji Wahono; Nadya Fadillah Fidhyallah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2026)
Research has widely demonstrated the importance of work-life balance and job stress in shaping employees' job satisfaction. However, empirical evidence from employees working in emergency response organizations remains limited. This study aims to examine the effects of work-life balance and job stress on job satisfaction among employees of the National Search and Rescue Agency (BASARNAS) Jakarta. This study employed a quantitative approach using a survey method. The respondents consisted of 116 BASARNAS Jakarta employees, selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results indicate that Work-Life Balance has a positive and significant effect on job satisfaction, with a path coefficient of 0.392, while job stress has a positive and significant effect on job satisfaction, with a path coefficient of 0.360. Furthermore, the coefficient of determination (R-Square) of 0.383 indicates that Work-Life Balance and job stress jointly explain 38.3% of the variance in employees' job satisfaction, while the remaining 61.7% is explained by other variables outside the research model. The findings are expected to provide practical insights for organizations in developing policies that promote Work-Life Balance, effectively manage job stress, and improve employee job satisfaction.